Philosophy in science: A name with a long intellectual tradition - Polak, Paweł Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
This paper presents Michael Heller’s notion of “philosophy in science” and re-introduces Michael Heller’s classical text that first presented this concept of philosophy entitled How is “philosophy in science” possible?. The paper discusses the historical context of Heller’s idea as it emerged from the discussions and works of the Krakow philosophical scene and discusses the basic tenants of this philosophy, its analytic character, the role of intellectual tradition in the development of this philosophy, and the critical role played by an interdisciplinary dialogue between philosophy, science, and theology. Despite the idea of philosophy in science having emerged about 40 years ago, this concept still inspires and fuels innovative research. The notion of “philosophy in science” lies at the foundations of the philosophy published in two journals: Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce) and Philosophy in Science.
Keywords: Michael Heller; philosophy in science; metaphilosophy; analytic philosophy; Lvov-Warsaw School; non-foundational philosophy; interdisciplinary research; science and religion